Chemical constituents and combined larvicidal effects of selected essential oils against anopheles cracens (Diptera: Culicidae) - Jitrawadee Intirach (2018)
A preliminary study on larvicidal activity against laboratory-colonized Anopheles cracens mosquitos revealed that five of ten plant oils at concentration of 100ppm showed 95-100% larval mortality. The essential oils of five plants, including Piper sarmentosum, Foeniculum vulgare, Curcuma longa, Myristica fragrans, and Zanthoxylum piperitum, were then selected for chemical analysis, dose-response larvicidal experiments, and combination-based bioassays. Chemical compositions analyzed by gas chromatography coupled to mass spectrometry demonstrated that the main component in the oil derived from P. sarmentosum, F. vulgare, C. longa, M. fragrans, and Z. piperitum was croweacin (71.01), anethole (63.00), ar-turmerone (30.19), safrole (46.60), and 1,8-cineole (21.27), respectively. For larvicidal bioassay, all five essential oils exerted promising efficacy in a dose-dependent manner and different performances on A. cracens after 24 hours of exposure. The strongest larvicidal potential was established from P. sarmentosum, followed by F. vulgare, C. longa, M. fragrans, and Z. piperitum, with LC50values of 16.03, 32.77, 33.61, 40.00, and 63.17ppm, respectively. Binary mixtures between P. sarmentosum, the most effective oil, and the others at the highest ratio were proved to be highly efficacious with a cotoxicity coefficient value greater than 100, indicating synergistic activity. Results of mixed formulations of different essential oils generating synergistic effects may prove helpful in developing effective, economical, and ecofriendly larvicides, as favorable alternatives for mosquito management. © Copyright 2012 Jitrawadee Intirach et al.